PERSEPSI PEMUSTAKA TERHADAP KINERJA PUSTAKAWAN DI PERPUSTAKAAN UNIVERSITAS NEGERI PADANG - Rahmat Fuadi; Ardoni Ardoni (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This study aims to describe the perceptions of users on the performance of librarians at the Padang State University Library. The type of research used is quantitative with descriptive methods. The population in this study is visitors from July to November 2022 at the Padang State University Library with a sample of 100 respondents. The sampling technique used is simple random sampling, namely the determination of the sample randomly. The research instrument uses a questionnaire as the main data. In addition, data collection techniques through observation, questionnaires. To test the prerequisite analysis using the validity test and reliability test. In analyzing the data of this study, the calculation of the mean and grand mean formulas is used. The results of this study indicate that the user's perception of the performance of librarians at the Padang State University Library with four indicators namely quality, quantity, timeliness, and commitment is categorized as good. Based on the results of an average score of 3.05. Located on an interval scale of 2.52-3.27.